2016
DOI: 10.1590/1519-6984.14314
|View full text |Cite
|
Sign up to set email alerts
|

The population density of Lymnaea columella (Say, 1817) (Mollusca, Lymnaeidae) an intermediate host of Fasciola hepatica (Linnaeus, 1758), in the Caparaó microregion, ES, Brazil

Abstract: The aim of this study was to monitor the population density of Lymnaea columella, an intermediate host of Fasciola hepatica, in various aquatic habitats and in drinking water in the area of the Instituto Federal de Educação, Ciência e Tecnologia do Espírito Santo, on Caparaó Microregion, municipality of Alegre, state of Espírito Santo, Brazil. Monthly samplings were performed at certain points between drainage areas and drinking water in cattle and goat production systems during the years 2010 to 2013. The mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…In another study carried out from 2010 to 2013 in Espirito Santo, reported two annual peaks of L. columella population. The increase in snail numbers was observed in March (2011 and and in November (2012), when precipitation was above the average (200 mm/year) -suggesting an increase in disease transmission (D'Almeida et al, 2016). Even though pluviosity is an indispensable condition for F. hepatica's life cycle, we demonstrate that the accumulated rain in SC was above the threshold to threaten the prevalence of the disease.…”
Section: Discussionmentioning
confidence: 67%
“…In another study carried out from 2010 to 2013 in Espirito Santo, reported two annual peaks of L. columella population. The increase in snail numbers was observed in March (2011 and and in November (2012), when precipitation was above the average (200 mm/year) -suggesting an increase in disease transmission (D'Almeida et al, 2016). Even though pluviosity is an indispensable condition for F. hepatica's life cycle, we demonstrate that the accumulated rain in SC was above the threshold to threaten the prevalence of the disease.…”
Section: Discussionmentioning
confidence: 67%
“…There were no studies that were conducted during the winter season only. Reviewed studies showed that P. columella snails were collected in abundance during the summer (rainy) season (Cardoso et al, 2006;Bargues et al, 2011;Prepelitchi et al, 2011;D'Almeida et al, 2016) as compared to the winter season (Bargues et al, 2011;Prepelitchi et al, 2011;D'Almeida et al, 2016). Results also showed that South American countries recorded the highest number of collected P. columella specimens globally involving field studies.…”
Section: Resultsmentioning
confidence: 98%
“…The overall prevalence of P. columella infected with Fasciola spp. varied from 0 to 100%, the lowest (0%) recorded in Brazil (Cardoso et al, 2006;D'Almeida et al, 2016), Argentina (Davies et al, 2014) and Colombia (Pereira et al, 2020), and the highest (100%) recorded in South Africa , Uruguay (Magalhães et al, 2004) and France (Pointier et al, 2007). Pseudosuccinea columella/Fasciola spp.…”
Section: Prevalence Of Fasciola Species Infection Intra-p Columella Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, more than one Galba/Fossaria species co-exist in other human endemic areas: G. truncatula, L. schirazensis and L. neotropica in Cajamarca, Peru (Bargues et al, 2012); L. cousini, L. neotropica, L. schirazensis and L. cubensis in Ecuador (Bargues et al, 2011b;Villavicencio et al, 2019); G. truncatula, L. cubensis and L. schirazensis in Venezuela (Bargues et al, 2011a); L. neotropica and L. viator in Argentina (Bargues et al, 2016); and G. truncatula and L. viator in Chile (Artigas et al, 2011). This high altitude scenario differs from fascioliasis in the lowlands, where fascioliasis is a veterinary problem in great part linked to the presence of a lymnaeid vector species not belonging to the Galba/Fossaria group as Pseudosuccinea columella, and human infection only appears in isolated cases, such as in Brazil (Maure et al, 1998;D'Almeida et al, 2016) and Uruguay (Bargues et al, 2017).…”
Section: Molecular Classification Of Lymnaeid Populationsmentioning
confidence: 99%